Sintesis Biodiesel dari Minyak Dedak Padi Memanfaatkan Katalis Padat dari Limbah Pengolahan Bauksit (Red Mud) - Arif Hidayat; Yosef Budiman; Maharani Fatimah Azzahra; Tsabita Yamna Putri R (Jurnal Inovasi Teknik Kimia, 2024)
In this study red mud, a solid waste from extraction process of bauxite mineral in Alumina Industry, was utilized as a solid catalyst for biodiesel production. In this study, biodiesel synthesis from reice bran oil was studied using red mud as solid catalysts. The catalyst was prepared by calcination. The performance of this catalyst will be evaluated in terms of molar ratio of methanol to (1:6–1:12), reaction temperature (35–65 °C), and catalyst loading (1-10%wt.). The results show that biodiesel yield is increased by increasing molar ratio of methanol to oil, reaction temperature and catalyst concentration. The optimum reaction conditions were obtained at 65 °C of reaction temperature, 1:12 of oil to methanol molar ratio, and 10% of catalyst amount. The highest biodiesel yield of 85.2% was obtained. The red mud catalyst has a promising candidate to be utilized in biodiesel production.